Substitution of maize with high fibre by-products in concentrates supplemented to dairy cows grazing kikuyu/ryegrass pasture during spring - Lingnau, Werner August Leonhard (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Animal Sciences))--University of Stellenbosch, 2011.